EFFECT OF SOIL IRRIGATION WITH TWO TYPES OF SEAPLANT EXTRACT AND HUMIC ACID ON GROWTH, QUANTITY AND QUALITY OF YIELD IN LETTUCE (Lactuca sativa L.) - Mohammad Al-Habar; Hussien Jawad Moharm Al-Bayati (Mesopotamia Journal of Agriculture)
This research was conducted during winter growing season of 2011-2012 at the vegetable Farm Hort. & Land Scape Design Department, Colloge of Agriculture and Forestry, Mosul Universty,to study the effect of soil irrigation with two seaplant extracts at two concentrations for each: Alga600 at 2 and 4 gm/ L and Algamix at 3 and 6 ml/ L in addition to humic acid at 3 and 6 ml/ L, the Chemical fertilizer, and control (non- fertilizer) treatments on growth and yield components of lettuce.The experiment involved 8 treatments implemented Randomized Complet Block Design (RCBD) with three replications Results indicated that application of Algamix at concentration 3ml/ L significantly increased leaf area/ plant, head length, stem length, and wiegth, whereas the same seaplant extract at concentration of 6 ml/ L increased the dry matter percentage of leaves, percentage of head folding, average weight of total and marketable/head, total and marketable head yield.